Injection-site pain after switching from somatrogon to somapacitan in children reporting pain or discomfort during once-weekly growth hormone therapy: a prospective single-arm switch study - Hideyuki Iwayama; Kohei Kawahara; Sachiko Kitagawa; Ryosuke Miyamoto; Junko Takagi; Yoshinori Ito; Akihisa Okumura (Frontiers in Endocrinology, 2026)
Background Once-weekly growth hormone (GH) formulations, such as somatrogon and somapacitan, may reduce the burden of treatment, but injection-site pain can affect treatment preference. Clinical data on patient-reported injection-site pain and preference after switching between once-weekly GH formulations remain limited, particularly in children who experience injection-site pain. Objective To describe changes in perceived injection-site pain and treatment preference after switching from somatrogon to somapacitan in children who reported injection-site pain or discomfort during somatrogon therapy. Methods This prospective single-arm switch study included 19 children with GH deficiency who had received somatrogon for at least 4 weeks, reported injection-site pain or discomfort during routine clinical care, and agreed to switch to somapacitan. Pain scores for prior somatrogon use and current somapacitan use were assessed once after at least 4 weeks of somapacitan treatment, using the Numerical Rating Scale and/or Faces Rating Scale according to age. A 5-point Likert questionnaire evaluated device usability, pain at needle insertion, pain during injection, pain after injection, and treatment preference. Paired t-tests and binomial tests were used for the main analyses, and Wilcoxon signed-rank tests were performed as sensitivity analyses for paired pain-score comparisons. Results The mean age was 9.6 ± 2.6 years. Diagnoses included isolated GH deficiency (n = 17) and panhypopituitarism after craniopharyngioma surgery (n = 2). Pain scores decreased after switching (Numerical Rating Scale: 6.5 ± 2.6 vs 1.6 ± 1.7; Faces Rating Scale: 3.8 ± 1.1 vs 1.1 ± 1.1; both p < 0.001). All participants preferred continued use of somapacitan (p < 0.001), and questionnaire responses favored somapacitan for pain at needle insertion and pain during injection. Conclusion In children who reported injection-site pain or discomfort during somatrogon therapy and agreed to switch, pain scores and treatment preference improved after switching to somapacitan. These findings support considering a switch to another once-weekly GH formulation when injection-site pain affects treatment preference.